Tuina for peripherally-induced neuropathic pain: A review of analgesic mechanism - Zhi-Feng Liu; Hou-Rong Wang; Tian-Yuan Yu; Ying-Qi Zhang; Yi Jiao; Xi-You Wang (Frontiers in Neuroscience, 2022)
Peripherally-induced neuropathic pain (pNP) is a kind of NP that is common, frequent, and difficult to treat. Tuina, also known as massage and manual therapy, has been used to treat pain in China for thousands of years. It has been clinically proven to be effective in the treatment of pNP caused by cervical spondylosis, lumbar disc herniation, etc. However, its analgesic mechanism is still not clear and has been the focus of research. In this review, we summarize the existing research progress, so as to provide guidance for clinical and basic studies. The analgesic mechanism of tuina is mainly manifested in suppressing peripheral inflammation by regulating the TLR4 pathway and miRNA, modulating ion channels (such as P2X3 and piezo), inhibiting the activation of glial cells, and adjusting the brain functional alterations. Overall, tuina has an analgesic effect by acting on different levels of targets, and it is an effective therapy for the treatment of pNP. It is necessary to continue to study the mechanism of tuina analgesia.